Strategi Kreatif Program Mustang Morning Squad dalam Mempertahankan Eksistensinya - Della Fahmi Fajarwati; Agustrijanto (UNIVERSITAS KALBIS, 2022)
Rapid technological developments make radio competing to create interesting programs. But it's not only interesting, but how the program is able to last a long time in the air and is able to retain its listeners. As one of the radio broadcasts in Jakarta, of course, Mustang Radio has prepared several superior creative program designs, one of which is Mustang Morning Squad. This study aims to determine the creative strategy formed in the Mustang Morning Squad Program in maintaining its existence. This study uses a qualitative research approach with a case study method. In this research, the researcher uses constructivism paradigm. The results of the research findings are, at the planning stage of the Mustang Morning Squad program using creative concepts, creative content, creative broadcasters, and creative promotions to maintain its existence.